2022
DOI: 10.14202/vetworld.2022.1269-1282
|View full text |Cite
|
Sign up to set email alerts
|

In vivo test of Vibrio alginolyticus and Vibrio harveyi infection in the humpback grouper (Cromileptes altivelis) from East Java Indonesia

Abstract: Background and Aim: The need for fish seeds resistant to bacterial and viral infections has encouraged studies on the molecular pathogenesis mechanism of Vibrio bacteria, such as Vibrio alginolyticus and Vibrio harveyi, regarding the receptor organs, protein adhesion mechanisms, and antibody responses of the humpback grouper. This study aims to confirm the characteristics of the specific proteins expressed in the receptor organ of the humpback grouper (Cromileptes altivelis) using the expression of V. alginoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Austin and Austin (2016), Park et al (2012) and Susanti et al (2016) stated that fish infected with Edwardsiella tarda shows some clinical signs of hemorrhage in organs, exophthalmia (protruding eyes), opacity of the eyes, distended abdomen, bloody ascites, and enlarged spleen and kidneys. Similar to current findings, fish injected with S. agactiae bacteria the Vibrio alginolyticus bacteria (Yanuhar et al, 2022); and E. cloacae (Sekar et al, 2008) revealed the same results that the same damages also occurred in fish kidneys.…”
Section: Discussionsupporting
confidence: 90%
“…Austin and Austin (2016), Park et al (2012) and Susanti et al (2016) stated that fish infected with Edwardsiella tarda shows some clinical signs of hemorrhage in organs, exophthalmia (protruding eyes), opacity of the eyes, distended abdomen, bloody ascites, and enlarged spleen and kidneys. Similar to current findings, fish injected with S. agactiae bacteria the Vibrio alginolyticus bacteria (Yanuhar et al, 2022); and E. cloacae (Sekar et al, 2008) revealed the same results that the same damages also occurred in fish kidneys.…”
Section: Discussionsupporting
confidence: 90%
“…infection is the dominant cause of vibriosis outbreaks in grouper aquaculture. Affected grouper typically manifested skin ulceration and haemorrhage and has a low survival rate, leading to a decline in aquaculture productivity (Sheikh et al., 2022; Yanuhar et al., 2022). In the present study, the response of hybrid groupers to V. alginolyticus infection varied among individuals, which is consistent with previous studies showing that different grouper fingerlings could either gain resistance or be susceptible to Vibrio sp.…”
Section: Discussionmentioning
confidence: 99%
“…V. alginolyticus is a halophilic gram-negative bacterium with a curved (comma) shape with a length of about 1.4 -5.0 µm and a width of 0.3 -1.3 µm. V. alginolyticus is motile and has flagella with a protective sheath [34]. This species is a natural host of estuarine and marine waters and is widely reported to be a pathogen for various diseases [35], such as wound infections, virulence, gastroenteritis, and other diseases.…”
Section: Identification Of Symbiotic Bacteriamentioning
confidence: 99%